The influence of organisational justice on organisational citizenship behaviour of employees at a railway company in Johannesburg, Gauteng - Kgomo, Moratuwa (Vaal University of Technology, 2021)
In South Africa, rail transport is an important element to support economic development and this service is provided by the railway company as the focus of this study. Similar to other companies, the selected railway company depends on its employees as a crucial resource to execute duties aimed at the realisation of its objectives. For the company to remain successful, its employees must have positive behaviours and attitudes and have the ability to work in a fair and just environment. Organisational justice, as an indicator of a fair and just work environment, and organisational citizenship behaviour, influence work-related behaviours and attitudes and are critical for the smooth operation of any organisation. Currently, the railway company seems to have a high number of reported incidents relating to organisational citizenship behaviour including misconduct, disciplinary, criminal and/or civil action. This might be an outcome of employee perceptions of organisational justice. This study examines the relationship between organisational justice and organisational citizenship behaviour for the first time in the rail industry in South Africa. Drawing on the Social Exchange Theory, the primary aim of this study is to investigate employees’ perceptions of organisational justice and their effects on organisational citizenship behaviour in a railway company in Johannesburg, Gauteng. The study adopted a deductive research approach and a quantitative method was used to collect data. Utilising a structured questionnaire, respondents were solicited to provide their demographic variables and their responses to four different measurement scales, namely procedural justice, distributive justice, interactional justice and organisational citizenship behaviour using a seven-point Likert scale ranging from 1=strongly disagree to 7=strongly agree. Using convenience sampling, questionnaires were distributed to 400 identified employees of the railway company in Johannesburg, Gauteng. A total of 378 questionnaires were returned and this constituted the sample size of the study. The Spearman’s rho correlation coefficient was used to find the strength of relationships with the use of the Statistical Package for Social Sciences (SPSS) version 25.0. To assess the employees' perceptions of organisational justice, their levels of organisational citizenship behaviour and the relationship between the constructs, descriptive statistical analysis, correlation and regression analysis were used. Based on the findings, the results of the correlation analysis revealed no significant relationships between all three dimensions of organisational justice (procedural justice, distributive justice, interactional justice) and organisational citizenship behaviour. Regression analysis also resulted in no predictive relationships between organisational justice and organisational citizenship behaviour. Evidence indicates that the fairness of distribution, procedures and interactions are not the key contributors in affecting the level of organisational citizenship behaviour of employees at the railway company. The study makes various recommendations including that management should treat employees fairly and equally and apply fair decision-making processes with fair outcomes. Additionally, to improve, increase and keep the standard of OCB, an organisational policy on organisational justice should be in place, which must constantly be updated. Research on OJ and OCB is still limited, particularly in the field of rail transport, as this study is the first and only study that has been conducted in South Africa. This represents an opportunity for academics and labour relations practitioners to further engage in research on antecedents and outcomes of organisational behaviour in the railway industry.
M. Tech. (Department of Labour Relations Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Organisational justice; Procedural justice; Distributive justice; Interactional justice; Organisational citizenship behaviour; Dissertations, Academic -- South Africa.; Organizational justice -- South Africa -- Gauteng.; Citizenship -- South Africa -- Gauteng.; Railroads -- South Africa -- Gauteng.; Organizational behavior -- South Africa -- Gauteng.; Railroads -- Employees -- South Africa -- Gauteng.